Autoimmune Hemolytic Anemia Combined with Sepsis After Abdominal Trauma Surgery - Gil Seong Moon; Young Un Choi; Hongjin Shim; Ji Young Jang (Journal of Acute Care Surgery, 2021)
Intra-abdominal infection is a common, serious complication in patients undergoing emergency abdominal surgery following blunt abdominal trauma. Infectious conditions increase the incidence of autoimmune hemolytic anemia (AIHA), but reports of AIHA occurring after abdominal trauma surgery are rare. Therefore, we report a case of sepsis due to fasciitis and AIHA after abdominal trauma surgery which was successfully managed following the appropriate treatment of both conditions.